Taxpayer Compliance on Micro, Small and Medium Enterprises Individual Taxpayer in Surakarta - Mujiyati Mujiyati; Galih Saras Sekarwangi; Indarti Diah Palupi (Universitas Muhammadiyah Surakarta, 2020)
This study aims to examine the effect of taxation regulations understanding, tax knowledge, tax sanctions, service quality and tax administration system modernization to the tax compliance of Micro Small and Medium Enterprises (MSME) individuals Taxpayer. This study uses a quantitative method with the respondents are MSME individual taxpayers which were registered at the Small Tax Office (KPP Pratama) in Surakarta. The accidental sampling method are used with a total sample collected are 99 respondents. This study also uses multiple linear regression models as data analysis techniques. The results of this study indicate that tax regulations understanding, tax knowledge, tax sanctions, and service quality affect the tax compliance of MSME individuals Taxpayer. Meanwhile, the modernization of the tax administration system does not influence the compliance of taxpayers on MSME individuals.